Development of an activated carbon‐supported zero‐valent iron catalyst (AC‐Fe0) for enhancing degradation of reactive brilliant orange and reducing iron sludge production. Issue 4 (19th February 2016) - Li, Dongyu; Zhu, Jishu; Wu, Jinhua; Yin, Weizhao; Liang, Hao; Lin, Guanghui
Abstract : Pure zero‐valent iron (ZVI) has poor catalytic capacity due to its agglomeration and slow corrosion rate in neutral solution and hence requires acid condition for heterogeneous Fenton reaction. In this study, we develop an activated carbon (AC)‐supported ZVI catalyst (AC‐Fe 0 ) that was prepared with a one‐step reductive roasting method by employing AC as a reductant and supporting matrix. The constructed AC‐Fe 0 was then used for Fenton degradation of an azo dye reactive brilliant orange (X‐GN). Analyses from multiple characterization techniques (e.g., scanning electron microscopy, X‐ray diffraction, and Brunnaer‐Emmett‐Teller) show that ZVI particles with a diameter of about 5 μm were dispersed on the surface and pores of the AC. We show that the AC‐Fe 0 could be used as a highly effective catalyst for Fenton degradation of X‐GN. A nearly unity efficiency of X‐GN decoloration was achieved within 80 min reaction time under neutral solution condition that was attributed to the well‐dispersion of ZVI particles on the AC and the formation of numerous galvanic cells between the ZVI and the AC. The decoloration of X‐GN was found to follow the pseudo‐first order kinetics and the apparent rate constant was measured to be 6.5 × 10 −2 min −1 at 30°C. We conclude that this newly‐developed AC‐Fe 0 technique greatly reduces the generation of massive iron‐containing sludge as the remaining ferric ion in the solution was minimized (<1 mg L −1 ) after the reaction. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 949–956, 2016